The Decision to Go Public and Business Group Affiliation: Evidence from India. (December 2022) - Sekhar, C. Suja; Lukose, P. J. Jijo
Using a comprehensive sample of Indian stock market listings from 2000 to 2014, we examine the effect of business group (BG) affiliation on the decision to go public. Supporting the internal capital markets hypothesis, we find that BG firms are less likely to go for initial public offerings (IPOs). Compared to stand-alone firms, BG firms that go public are older and less profitable. Further, this article elucidates the dynamics of the decision to go public within BGs (with multiple unlisted eligible affiliates in their portfolio) as extant models fail to explain the same adequately. We examine the relative importance of reputation, capital raising, and control considerations on the decision to go public. We find that the affiliate that invests in other group affiliates' financial assets is more likely to be taken public. Affiliates that are net receivers of intragroup support are less likely to list. BG's reputation has a positive impact on the choice of the affiliate to list. JEL Classifications: G30, G32